2022
DOI: 10.3390/catal12050557
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Recalcitrant Pollutants of Greywater

Abstract: These days, many countries have a water shortage and have limited access to clean water. To overcome this, a new treatment is emerging, namely, the photocatalytic processing of greywater. Photocatalytic processes to remove the organic matter from different greywater sources are critically reviewed. Their efficiency in degrading the organic matter in greywater is scrutinized along with factors that can affect the activity of photocatalysts. Modified TiO2, ZnO and TiO2 catalysts show great potential in degrading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…It has been reported that, with high initial concentrations, the photocatalytic performance can be diminished, whereas low concentrations help maintain, and even to improve, the photoactivity of the catalyst. This can be attributed to the adsorption of the pollutant over the surface of the photocatalysts, saturating it and hindering the generation of hydroxyl radicals (OH•), which are usually the chemical species that rule photocatalytic tests 45,46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, with high initial concentrations, the photocatalytic performance can be diminished, whereas low concentrations help maintain, and even to improve, the photoactivity of the catalyst. This can be attributed to the adsorption of the pollutant over the surface of the photocatalysts, saturating it and hindering the generation of hydroxyl radicals (OH•), which are usually the chemical species that rule photocatalytic tests 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the adsorption of the pollutant over the surface of the photocatalysts, saturating it and hindering the generation of hydroxyl radicals (OH•), which are usually the chemical species that rule photocatalytic tests. 45,46 Fluorescence tests have been developed as a fast analysis for determining the generation of hydroxyl radicals in aqueous media (Supporting Information, Scheme S1). When comparing the half-life time obtained with the new ZnO and the recovered one used in the third reaction cycle, the degradation of the phenol becomes slower; consequently, a longer time is required to achieve half the degradation of its initial concentration (either 5 or 50 ppm).…”
Section: Discussionmentioning
confidence: 99%
“…A Photocatalytic process occurs when the light interacts with the surface of semiconductor materials, the so-called photocatalysts, allowing the photo redox process. During this process, there must be at least two simultaneous reactions occurring, oxidation from photogenerated holes and reduction from photogenerated electrons ( Figure 3 ) [ 36 , 37 , 38 ].…”
Section: Basic Principles Of Photocatalysismentioning
confidence: 99%
“…This catalytic activity stems from the generation of electron-hole pairs upon exposure to UV light, which subsequently triggers redox reactions leading to the breakdown of complex pollutant molecules into simpler and less harmful compounds [18]. This photocatalytic degradation mechanism presents a sustainable and energy-efficient route to neutralize recalcitrant pollutants, showcasing the potential of these materials to transform the landscape of wastewater treatment practices [18,19].…”
Section: Introductionmentioning
confidence: 99%